Social constructivism, social practice theory and sociocultural theory: relevance and rationalisations in mathematics education. detail, reflection and synthesis - Jaworski, Barbara (NOMAD Nordic Studies in Mathematics Education, 2000)
This paper contains detail from, reflection on and synthesis of the Conference held in Gausdal, Norway, in March, 2000, on ’Social Constructivism, Social Practice Theory and Sociocultural Theory: Relevance and Rationalisations in Mathematics Education’.